Distribution, source identification, ecological and health risks of heavy metals in surface sediments of the Rupsa River, Bangladesh. (2nd January 2021) - Proshad, Ram; Kormoker, Tapos; Islam, Saiful
Abstract: The present study was conducted to assess the pollution level and distribution of heavy metals and their ecological and health risk in sediments of the Rupsa River, Bangladesh. Heavy metals were measured by using inductively coupled plasma mass spectrometer. The mean concentration of Cr, Ni, Cu, As, Cd, and Pb in sediments was 25.26, 42.40, 68.81, 9.31, 3.78, and 32.57 mg/kg, respectively. Metals in sediment during winter were higher than summer season. Multivariate principal component analysis revealed significant anthropogenic contributions of Cr, Ni, As and Cd in sediment. The enrichment factor (EF), geoaccumulation index (Igeo ), pollution load index (PLI), and contamination factor (C i f ) demonstrated that most of the sediment samples were heavily contaminated by Cd. The sum of toxic units in most of the sampling sites during winter season was greater than 4, indicating a moderate to serious toxicity of heavy metals in sediment. In view of the potential ecological risk, sediments of Rupsa River showed low to very high potential ecological risk. The chronic daily intake of metals were higher than oral RfD which was the result of metal contamination. The total hazard index for adult and children, about 100% sampling location possess (HI > 1) indicating pose non-cancer risk. The carcinogenic risks from As and Pb at all sites via ingestion and dermal contact were higher than acceptable ranges (10 −4 ). This study suggested that more attention should be directed to the comprehensive risk assessment of heavy metals of this riverine aquatic environment.